Cobalt Phosphate Nanoparticles Embedded Nitrogen and Phosphorus-Codoped Graphene Aerogels as Effective Electrocatalysts for Oxygen Reduction - Xuan, Li-Li; Liu, Xiao-Jun; Wang, Xue (Frontiers in Materials, 2019)
Developing cost-efficient and high-performance non-noble metal electrocatalysts for oxygen reduction reaction is of great significance for large-scale commercialization of fuel cells. Here, a novel cobalt phosphate-embedded nitrogen and phosphorus co-doped graphene aerogel (labeled as Co3(PO4)2/N,P-GA) is prepared via combination of a facile hydrothermal apporoach with a pyrolysis procedure. The obtained Co3(PO4)2/N,P-GA catalysts display excellent catalytic performance in base media, with optimal Co3(PO4)2/N,P-GA-900 (the material prepared at pyrolysis temperature of 900 ºC) showing better catalytic activity for ORR than other as-obtained contrast materials in terms of the onset potential, half-wave potential and diffusion-limiting current density, even superior to the commercial Pt/C catalyst. Furthermore, the Co3(PO4)2/N,P-GA also possesses good methanol tolerance and excellent durability. The superior performance of Co3(PO4)2/N,P-GA is attributed to the hierachical porous structure, large BET surface area, N,P-codoping, cobalt phosphate-based nanoparticles loaded on graphene nanosheets, and synergistic effects between the doped active species. Therefore, it is expected to replace Pt/C as a promising fuel cell catalyst in alkaline direct methanol fuel cells.